2010
DOI: 10.1007/s00595-009-4081-y
|View full text |Cite
|
Sign up to set email alerts
|

Superdrainage of the ileocolic vein to the internal jugular vein interposed by an inferior mesenteric vein graft in replacing the esophagus with the right hemicolon

Abstract: The fear of serious complications, such as a necrotic conduit caused by an impaired blood circulation can arise when replacing the esophagus with an intestinal conduit. The aim of this paper is to present effective superdrainage of an intestinal conduit using an inferior mesenteric vein (IMV) interposition graft. In 2008, we performed superdrainage of the ileocolic vein to the internal jugular vein interposed by an IMV graft in replacing the esophagus with the right hemicolon for advanced thoracic esophageal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…We believe that these procedures are time‐consuming and invasive in contrast with harvesting a graft. For example, the IMV graft may be harvested from the mesocolon in under 10 minutes 25 . Although an additional anastomosis is required for this procedure, adequate blood drainage is accomplished by directly anastomosing a drainage vein to the internal jugular vein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We believe that these procedures are time‐consuming and invasive in contrast with harvesting a graft. For example, the IMV graft may be harvested from the mesocolon in under 10 minutes 25 . Although an additional anastomosis is required for this procedure, adequate blood drainage is accomplished by directly anastomosing a drainage vein to the internal jugular vein.…”
Section: Discussionmentioning
confidence: 99%
“…Veins were anastomosed in an end‐to‐side manner when the internal jugular vein was selected as an outflow vein. The vein graft was interposed between the veins when the distance between the veins was too long 25 . For instance, an inferior mesenteric vein (IMV) graft, approximately 10 cm in length, was harvested from the mesocolon and immersed in heparinized saline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some surgeons have reported the utility of both supercharge and superdrainage in cases of colon interposition after esophagectomy [18]. Shirakawa et al [19] reported that the supercharge technique for colonic interposition was advantageous with regards to peri-operative complications and contributes to the patient's quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Other candidate drainage veins are the anterior cervical vein, the external jugular vein, and so forth. Because a direct anastomosis of the ileocolic vein to the internal jugular vein cannot be accomplished in most cases, we have recently used an inferior mesenteric vein graft interposition to fill the gap between the two vessels [32].…”
Section: Supercharge and Superdrainage Of A Right Hemicolon Conduit Fmentioning
confidence: 99%